2019
DOI: 10.1159/000500267
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of Activity-Dependent Homer in Synaptic Plasticity

Abstract: Alterations in synaptic signaling and plasticity occur during the refinement of neural circuits over the course of development and the adult processes of learning and memory. Synaptic plasticity requires the rearrangement of protein complexes in the postsynaptic density (PSD), trafficking of receptors and ion channels and the synthesis of new proteins. Activity-induced short Homer proteins, Homer1a and Ania-3, are recruited to active excitatory synapses, where they act as dominant negative regulators of consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 162 publications
(244 reference statements)
2
79
0
Order By: Relevance
“…whether the features of a synapse influence the local distribution and abundance of the elements of the secretory pathway, or their proximity to the synapse, we designed a high throughput experiment that enabled simultaneous super-resolution imaging of multiple proteins and parameters in cultured hippocampal neurons. The parameters selected to define synapses were the fluorescence signal intensities of the following: homer, a postsynaptic structural marker 44 ; vGLUT1, a marker of the entire pre-synaptic vesicle population of excitatory nerve terminals in these cultures 46 ; and live labelling of SYT1 for identifying only the actively recycling synaptic vesicles in pre-synaptic boutons 48 . While the first two markers provide indications on the strength of the synapse, the latter is a proxy for synaptic activity (Fig.…”
Section: Secretory Pathway Elements Are Present In Proximity To Post-mentioning
confidence: 99%
See 1 more Smart Citation
“…whether the features of a synapse influence the local distribution and abundance of the elements of the secretory pathway, or their proximity to the synapse, we designed a high throughput experiment that enabled simultaneous super-resolution imaging of multiple proteins and parameters in cultured hippocampal neurons. The parameters selected to define synapses were the fluorescence signal intensities of the following: homer, a postsynaptic structural marker 44 ; vGLUT1, a marker of the entire pre-synaptic vesicle population of excitatory nerve terminals in these cultures 46 ; and live labelling of SYT1 for identifying only the actively recycling synaptic vesicles in pre-synaptic boutons 48 . While the first two markers provide indications on the strength of the synapse, the latter is a proxy for synaptic activity (Fig.…”
Section: Secretory Pathway Elements Are Present In Proximity To Post-mentioning
confidence: 99%
“…The amplitude of the post-synaptic response, commonly referred to as the synaptic strength, can be modulated by changes at both the pre-and post-synaptic levels (for reviews see [37][38][39][40][41][42] ). At the post-synapse, larger post-synaptic densities (PSD) reflect a higher number of functional receptors, and hence a stronger and more potentiated synapse 43,44 . At the pre-synaptic level, synaptic strength can be modulated, among others, by the availability of vesicles and release machinery proteins 45 .…”
mentioning
confidence: 99%
“…The Group I mGluRs play roles in both synaptic potentiation and depression, via agonist-dependent and -independent signaling, and it has been shown that enhancing mGluR5 activation with positive allosteric modulators enhances LTP (48). Long-and short-isoform Homer1 interact with an intracellular domain of mGluR1/5 and differentially modulate signaling through downstream effectors (52). CDK5 phosphorylates the Homer1-binding domain of mGluR5, increasing its affinity for HOMER1 and altering its trafficking and association within the PSD (28).…”
Section: Deletion Of Sin3a From Forebrain Excitatory Neurons Enhancesmentioning
confidence: 99%
“…Among the short Homer proteins, only the short Homer1 splice isoforms, namely Homer1a and Ania-3, have been characterized in terms of expression and function [7,78,79]. Unlike the long Homer isoforms, which are constitutively expressed in both neuronal and non-neuronal tissues [3,6,7,[28][29][30][31][32][33]78,79], Homer1a and Ania-3 have been shown to be neuron-specific splice isoforms [1,2,78] and to be rapidly and transiently upregulated upon neuronal stimulation [1][2][3]6,78,79]. We found that at E14.5, in addition to other brain regions, the hippocampal formation was enriched with Homer1 mRNA and protein.…”
Section: The Three Homer Family Members Are Expressed Ubiquitously Inmentioning
confidence: 99%